Servants of nature : a history of scientific institutions, enterprises, and sensibilities - Pyenson, Lewis; Sheets-Pyenson, Susan, 1949- (London : Fontana, 1999)
"Servants of Nature explores the interaction between scientific practice and public life from antiquity to the present. Drs Lewis Pyenson and Susan Sheets-Pyenson show how, in Asia, Europe and the New World, scientific expression has been allied closely with changes in three distinct areas of society: the institutions that sustain science; the moral, religious, political and philosophical sensibilities of scientists themselves; and the goal of the scientific enterprise."--BOOK JACKET. "Following the establishment of institutions of higher learning, scientific societies and museums, the authors trace how the bodies that determine scientific tradition and guide innovation have acquired their authority. They also consider how scientific goals have changed and they examine the relationship between scientists, militarists and industrialists in modern times."--BOOK JACKET.
Introduction: Science and Its Past -- Pt. I. Institutions. 1. Teaching: Before the Scientific Revolution. 2. Teaching: From the Time of the Scientific Revolution. 3. Sharing: Early Scientific Societies. 4. Watching: Observatories in the Middle East, China, Europe and America. 5. Showing: Museums. 6. Growing: Botanical Gardens and Zoos -- Pt. II. Enterprises. 7. Measuring: The Search for Precision. 8. Reading: Books and the Spread of Ideas. 9. Travelling: Discovery, Maps and Scientific Expeditions. 10. Counting: Statistics. 11. Killing: Science and the Military -- Pt. III. Sensibilities. 12. Participating: Beyond Scientific Societies. 13. Appropriating: Science in Nations Beyond Europe. 14. Believing: Science and Religion. 15. Knowing: Progressing and Proclaiming. 16. Knowing: Relativizing.
Includes bibliographical references and index.
Keywords: Science -- Social aspects -- History; Science -- Study and teaching -- History